Drought Stress Responses of Sunflower Germplasm Developed after Wide Hybridization - Roumiana Dimova Vassilevska-Ivanova; Lydia Shtereva; Ira Stancheva; Maria Geneva (Turkish Journal of Agriculture: Food Science and Technology)
Response of sunflower germplasms viz. cultivated sunflower H. annuus and two breeding lines H. annuus x T. rotundifolia and H. annuus x V. encelioides developed after wide hybridization were used for identification of drought tolerant sunflower genotypes at the seedling growth stage. Three water stress levels of zero (control), -0.4, and -0.8 MPa were developed using polyethyleneglycol-6000 (PEG-6000). Physiological and biochemical stress determining parameters such as root and shoots length, fresh weight, antioxidant enzyme activities (superoxide dismutase (SOD), catalase (CAT), guaiacol peroxidase (GPO), ascorbate peroxidase (APX) and antioxidant metabolite content (total antioxidant capacity, total phenols and total flavonoids content) were compared between seedlings of all three genotypes. Results revealed that sunflower genotypes have similar responses at two osmotic potentials for shoot and root length and fresh weight. The data also showed that drought stresss could induce oxidative stress, as indicated by the increase level of ascorbate peroxidase and guaiacol peroxidase at -04 MPa in H. annuus cv 1114. Although the activity of ascorbate peroxidase and guaiacol peroxidase was differentially influenced by drought, the changes of antioxidant enzyme activities such as catalase, superoxide dismutase, guaiacol peroxidase, and ascorbate peroxidase subjected to drought stress follow a similar pattern in both breeding lines, indicating that similar defense systems might be involved in the oxidative stress injury in sunflowers. Increase in content of phenols and flavonoids were detected for all three genotypes under stress, which showed that these were major antioxidant metabolites in scavenging cellular H2O2.